DEVELOPMENT OF TRENDS, INNOVATION AND EFFECTIVE DISTRIBUTION STRATEGIES IN INTERNATIONAL MARKETING - Ichwan Musa; Rezky Amaliah Hamka; Nur Atifah (Journal Management & Economics Review (JUMPER), 2023)
International marketing is a business strategy that involves expanding a company's marketing operations beyond its national borders. In the era of globalization and technological advances, international marketing is becoming increasingly important for companies wishing to expand their product or service range to international markets. This abstract discusses the concepts and challenges of international marketing and describes the benefits that can be obtained by companies that successfully implement this strategy. International marketing involves in-depth market research, understanding the culture and consumer habits of the target country, and adapting products and promotions accordingly. This abstract also explains the importance of business partnerships and effective distribution strategies in the context of international marketing. This closing abstract provides an overview of the development of trends and innovations in international marketing, including the use of digital technology and social media in reaching international audiences.